Pastor Rosing and missionary Julius Olsen with newly baptized East Greenlanders. Angmagssalik, ... : Pastor Rosing og missionær Julius Olsen med nydøbte Østgrønlændere. Angmagssalik ca. 1920 - Unknown (University of Southern California Digital Library (USC.DL), 2015)
Pastor Rosing and missionary Julius Olsen with newly baptized East Greenlanders. Angmagssalik, ca.1920.